Crystal structures of the GH6 Orpinomyces sp. Y102 CelC7 enzyme with exo and endo activity and its complex with cellobiose. Issue 12 (3rd December 2019) - Huang, Hsiao-Chuan; Qi, Liu-Hong; Chen, Yo-Chia; Tsai, Li-Chu
Abstract : Crystal structures and the enzymatic properties of the GH6 Orpinomyces sp. Y102 CelC7 enzyme suggest that this enzyme may perform enzymatic hydrolysis in the same way as cellobiohydrolases and endoglucanases. Abstract : The catalytic domain (residues 128–449) of the Orpinomyces sp. Y102 CelC7 enzyme ( Orp CelC7) exhibits cellobiohydrolase and cellotriohydrolase activities. Crystal structures of Orp CelC7 and its cellobiose‐bound complex have been solved at resolutions of 1.80 and 2.78 Å, respectively. Cellobiose occupies subsites +1 and +2 within the active site of Orp CelC7 and forms hydrogen bonds to two key residues: Asp248 and Asp409. Furthermore, its substrate‐binding sites have both tunnel‐like and open‐cleft conformations, suggesting that the glycoside hydrolase family 6 (GH6) Orp CelC7 enzyme may perform enzymatic hydrolysis in the same way as endoglucanases and cellobiohydrolases. LC‐MS/MS analysis revealed cellobiose (major) and cellotriose (minor) to be the respective products of endo and exo activity of the GH6 Orp CelC7.